Analisis Indeks Pembangunan Manusia Terhadap Pertumbuhan Ekonomi Kabupaten Bojonegoro - Azhari, Azhari; Muslinawati, Retno; Sakti, Tengku Muda Agam; Izah, Wizka Rif'atul (JURNAL DIMENSI, 2025)
This study aims to analyze the effect of the Human Development Index (HDI) on economic growth in Bojonegoro Regency. The HDI is measured through three main components, namely Average Length of Schooling (ALS), Life Expectancy (LE), and Per Capita Expenditure (PCE), which reflect the quality of education, health, and the standard of living of the community. This study uses secondary data from 2009 to 2023 obtained from the Central Statistics Agency. The analysis method used is multiple linear regression to test the influence of each independent variable on economic growth, measured through the Regional Domestic Product (RDP) at constant prices. The results indicate that the average years of schooling and life expectancy variables have no significant impact on economic growth, with positive and negative directions, respectively. Conversely, the per capita expenditure variable has a significant and positive impact on economic growth in Bojonegoro Regency. This finding underscores that aspects of consumption and purchasing power play a dominant role in driving regional economic growth. This study has important implications for the formulation of regional development policies, particularly in improving the quality of education and health services and strengthening the purchasing power of the community.